To end a presidency the power of impeachment - Tribe, Laurence H.; Matz, Joshua (New York, NY Basic Books, 2018)
"The history and future of our democracy's ultimate sanction, presidential impeachment, and a guide to how it should be used now. To End a Presidency addresses one of today's most urgent questions: when and whether to impeach a president. Laurence Tribe and Joshua Matz provide an authoritative guide to impeachment's past and a bold argument about its proper role today. In an era of expansive presidential power and intense partisanship, we must rethink impeachment for the twenty-first century. Of impeachments, one Constitutional Convention delegate declared, "A good magistrate will not fear them. A bad one will be kept in fear of them." To End a Presidency is an essential book for all Americans seeking to understand how this crucial but fearsome power should be exercised"-- Provided by publisher.
"This is a book about ending presidencies through the power of impeachment. It's also a book about fighting for the US Constitution and the democracy it protects. As such, this book is a general exploration of law, history, and politics bearing on the exercise of the impeachment power in the US Constitution. Our goal is to identify general principles and frameworks that should govern any impeachment analysis, in each chapter identifying important recurring questions and proposing a framework for how to think about them"-- Provided by publisher.
Why Impeachment? -- Impeachable Offenses -- To Impeach or Not to Impeach -- Congress, the Decider -- Impeachment Talk -- Impeachment, Incapacity, and Broken Politics.
Includes bibliographical references (pages 267-268) and index.
Keywords: Impeachments -- United States; Presidents -- Legal status, laws, etc. -- United States; Law -- Constitutional; Political science / -- Constitutions; Political science -- Government -- Legislative Branch; Political science -- Government -- Executive Branch; Law -- Government -- Federal; United States -- Politics and government -- 1989-.